Records management practices of international organizations in the Philippines a survey - Nofuente, Evelyn D. (1981)
This study is a descriptive survey of thirteen (13) international organizations based in the Philippines. It aims to survey established standards, procedures and techniques of records keeping practices of international organizations. It also aims to describe the processes by which these organizations plan the creation of records, determine the utilization of a records classification scheme, the reference activities of all records, the filing systems being used and to find out how many of these organizations have already established a records retention and disposition schedule, a vital records protection program and the existing procedures governing the preservation of records, its orderly retirement and the system being utilized to eliminate unnecessary duplication of documents. The normative survey method of research was employed using the questionnaire and interview techniques. Records administrators from thirteen (13) international organizations served as respondents.